A Pipeline for the Creation of Multimodal Corpora from YouTube Videos - Dykes, Nathan; Wilson, Anna; Uhrig, Peter (Proceedings of the 1st Workshop on Linguistic Insights from and for Multimodal Language Processing (LIMO 2023), 2023)
This paper introduces an open-source pipeline for the creation of multimodal corpora from YouTube videos. It minimizes storage and bandwidth requirements, because the videos themselves need not be downloaded and can re-main on YouTube’s servers. It also minimizes processing requirements by using YouTube’s automatically generated subtitles, thus avoiding a computationally expensive automatic speech recognition processing step. The pipeline combines standard tools and provides as its output a corpus file in the industry-standard vertical format used by many corpus managers. It is straightforwardly extensible with the addition of further levels of annotation and can be adapted to languages other than Englis
Keywords: automatic speech recognition; multimodal corpora